Linking Behavioral and Neurophysiological Indicators of Perceptual Tuning to Language - Fava, Eswen; Hull, Rachel; Bortfeld, Heather (Frontiers in Psychology, 2011)
Little is known about the neural mechanisms that underlie tuning to the native language(s) in early infancy. Here we review language tuning through the lens of language experience and introduce a new manner in which to conceptualize the phenomenon of language tuning: the relative speed of tuning hypothesis. This hypothesis has as its goal a characterization of the unique time course of the tuning process, given the different components (e.g., phonology, prosody, syntax, semantics) of one or more languages as they become available to infants. In this review, we first examine the established behavioral findings and integrate more recent neurophysiological data on neonatal development, which together demonstrate evidence of early language tuning given differential language exposure in utero. Next, we examine traditional accounts of sensitive and critical periods to determine how these constructs complement current data on the neural mechanisms underlying language tuning. We then synthesize the extant infant behavioral and imaging literatures on monolingual, bilingual, and sensory deprived tuning experience, thereby scrutinizing the effect of these three different language profiles on the specific timing, progression, and outcomes of language tuning. Finally, we discuss future directions researchers might pursue on this aspect of development, advocating our relative speed of tuning hypothesis as a useful framework for conceptualizing the complex process by which language experience shapes language sensitivity.